2002
DOI: 10.1023/a:1015728825642
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Neuropsychiatric problems, and how they interact to impact on quality of life (QOL) in brain tumor patients, are generally poorly understood. The objectives of this study were: (1) to document the prevalence of depression, fatigue, emotional distress, and existential issues in a sample of brain tumor patients (2) to examine the interconnectedness of these problems, and (3) to explore their relationship with disease-related variables and QOL. This is a cross-sectional, questionnaire-based survey of 73 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(81 citation statements)
references
References 39 publications
0
80
1
Order By: Relevance
“…In symptom cluster analysis, depression explained 26% of the variance in quality of life, and 56% of the variance in functional status in brain cancer patients [5]. Similarly, Pelletier et al found that the presence of depressive symptoms was the most significant predictor of quality of life in a sample of brain tumor patients [19]. This study did not utilize a discreet instrument for psychosocial distress, but utilized emotional distress as measured by the FACT-Br.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In symptom cluster analysis, depression explained 26% of the variance in quality of life, and 56% of the variance in functional status in brain cancer patients [5]. Similarly, Pelletier et al found that the presence of depressive symptoms was the most significant predictor of quality of life in a sample of brain tumor patients [19]. This study did not utilize a discreet instrument for psychosocial distress, but utilized emotional distress as measured by the FACT-Br.…”
Section: Introductionmentioning
confidence: 79%
“…The disease process itself contributes to fatigue, and brain tumor patients are highly likely to receive treatments, such as cranial irradiation, that are associated with high levels of fatigue. Fatigue has been noted in a number of studies in highgrade-glioma patients [1,19]. Depression has a high prevalence among patients with brain cancer, with depressive symptoms in one study being reported by 69 (95%) of 73 participants [5].…”
Section: Introductionmentioning
confidence: 95%
“…To further complicate this situation, patients must almost immediately make choices and decisions about complex treatment plans. Other issues that present challenges to survivors of brain tumors are fatigue and loss of stamina resulting from irradiation and chemotherapy, seizures and their treatments (anticonvulsants) which have been known to impact patient cognition [17], enormous financial drain due to loss of employment/ insurance coverage and medications not covered by insurance [18], one's ability to drive is often suspended which impacts patients' independence and often increases the sense of burden on social network, changes in body image due to corticosteroid use-cushingoid appearance along with weight gain, tensions in intimate relationships, changes in personality and behavior associated with mild brain injury, and symptoms suggestive of clinical depression [19]. To further complicate the experience, the prognosis for GBMs is poor relative to other cancers and even other types of brain tumors [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Mood issues that are potentially treatable may then be overlooked and undertreated 66. This can have serious negative consequences for glioma patients’ quality of life,67 and even their morbidity and survival 47,68…”
Section: Mood Issuesmentioning
confidence: 99%